Комплексні дослідження технологій, обладнання та систем автоматизації металургійного виробництва - Муравйова, І.Г. (Physico-technological Institute of Metals and Alloys, 2023)
The main stages of the formation of research topics of the department of technological equipment and control systems are shown. The analysis of the results of scientific activities of the three divisions of the department has been made. The main developments of a group of blast furnace machines are presented, which include: technology for loading a multicomponent charge; a complex mathematical model of the formation of multicomponent batches of charge materials, their loading into the bunker of the bell-less top (BLT), unloading from the bunker and distribution on the surface of the mound; intelligent decision support system for blast furnace management; new methods of control and management of blast furnace using information from modern automated control systems. The main directions of cooperation with metallurgical enterprises of the industry are shown. The main directions of research by a group of developing technologies and equipment for the preparation of charge materials are presented, covering theoretical and experimental studies of the influence of physic-mechanical and technological characteristics of finely charged charge materials on the pressing process, the quality of briquettes and their metallurgical properties, as well as the creation of technical solutions for mechanical equipment for briquetting. The results of research and development of new methods for diagnosing, improving the operating conditions of mills are presented together with the features of technologies, methods for assessing the stability of equipment and the technological process, which are performed by employees of the rolling equipment dynamics group.